Two new species of the genus tshurtshurnella kusnezov (Hemiptera, Auchenorrhyncha, Fulgoroidea: Issidae) from eastern anatolia1 - Gnezdilov, V.M.; Özgen, I. (Pleiades Publishing, 2018)
Tshurtshurnella bicolorata sp. n. and T. curtulum sp. n. are described from Elazığ and Malatya provinces of Turkey. T. bicolorata sp. n. is well distinguished from the other species of the genus by the presence of two color forms in males and females and T. curtulum sp. n., by darkly colored females and pale males. Also these new species differ from the other species of the genus in the characters of the structure of the male genitalia. © Pleiades Publishing, Inc., 2018.